2010
DOI: 10.1016/j.topol.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative spectrum of ultrametric Banach algebras of continuous functions

Abstract: International audienceLet $K$ be an ultrametric complete field and let $E$ be an ultrametric space. Let $A$ be the Banach $K$-algebra of bounded continuous functions from $E$ to $K$ and let $B$ be the Banach $K$-algebra of bounded uniformly continuous functions from $E$ to $K$. Maximal ideals and continuous multiplicative semi-norms on $A$ (resp. on $B$) are studied by defining relations of stickness and contiguousness on ultrafilters that are equivalence relations. So, the maximal spectrum of $A$ (resp. of $B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1
1

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(43 citation statements)
references
References 14 publications
4
39
0
Order By: Relevance
“…First, we generalize results obtained in [8] and [9] to some Banach algebras of uniformly continuous bounded functions which we call semi-compatible and C-compatible and which are related to the contiguity relation yet considered in these papers. Actually, considering such an algebra S, we describe interactions between the contiguity relation defined on ultrafilters on IE and maximal ideals or the multiplicative spectrum of S. We prove that the Shilov boundary of S is the multiplicative spectrum itself.…”
Section: Introduction and General Results In Topologymentioning
confidence: 81%
See 2 more Smart Citations
“…First, we generalize results obtained in [8] and [9] to some Banach algebras of uniformly continuous bounded functions which we call semi-compatible and C-compatible and which are related to the contiguity relation yet considered in these papers. Actually, considering such an algebra S, we describe interactions between the contiguity relation defined on ultrafilters on IE and maximal ideals or the multiplicative spectrum of S. We prove that the Shilov boundary of S is the multiplicative spectrum itself.…”
Section: Introduction and General Results In Topologymentioning
confidence: 81%
“…We will denote by l G(IE) the family of uniformly open subsets of IE. In [8] and [13], dealing with the Banaschewski compactification of IE the authors considered the Boolean ring of clopen sets of IE (with the usual addition ∆ and multiplication ∩). In Section 4 we will consider the Boolean ring of uniformly open sets.…”
Section: Introduction and General Results In Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…In [2], [4], [5], [6] we studied several examples of Banach IK-algebras of functions and showed that for each example, each maximal ideal is defined by ultrafilters [1], [7], [8] and that each maximal ideal of finite codimension is of codimension 1: that holds for continuous functions [4] and for all examples of functions we examine in [2], [5], [6]. Thus, we can ask whether this comes from a more general property of Banach IK-algebras of functions, what we will prove here.…”
mentioning
confidence: 99%
“…Concerning semi-compatible algebras, it just comes from Theorem 3.1 in [2]. Concerning semi-adimissible algebras, we can generalize Theorem 5.1 in [4] and then Corollary 5.2 to any semi-admissible algebras. Thus, we obtain Theorem A:…”
mentioning
confidence: 99%